A low resistance efb battery separator and method of making the same

CN122931233APending Publication Date: 2026-10-16SEPARATOR TECH (BENGBU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611203630.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,小分子偶联剂在隔膜制备的萃取工序中易随填充油流失,而MAH-g-PE的极性接枝基团在强酸性电解液中长期浸泡后存在水解风险,导致界面结合力下降,填料团聚问题在电池后期使用中重新显现,此外,此类相容剂的加入增加了配方复杂性和成本,且可能在电池体系中引入杂质

Benefits of technology

本发明电池隔膜采用的功能化复合填料是由中空介孔二氧化硅、实心二氧化硅和氨基化氮化硼纳米片共同经超支化含氟聚合物改性而得,利用中空介孔二氧化硅提供的有序介孔通道与实心二氧化硅提供的辅助造孔实现低电阻、利用氨基化氮化硼纳米片的二维片层网络实现高抗穿刺和低热收缩、利用超支化含氟聚合物的统一壳层实现自分散免相容剂,三种功能协同作用,全面解决了现有EFB电池聚乙烯隔膜电阻高、强度低、填料易团聚、热尺寸稳定性差的技术难题,使得制备的隔膜,能够满足EFB启停电池隔膜大电流充放电工况下低电阻的使用要求,具有极强的工业应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a low-resistance EFB battery diaphragm and a preparation method thereof, the diaphragm is prepared from raw materials comprising the following components: polyethylene resin: 135-165 parts by mass; functionalized composite filler: 200-250 parts by mass; filling oil: 340-460 parts by mass; initiator: 0.2-1 parts by mass; the functionalized composite filler is obtained by modifying hollow mesoporous silica, solid silica and aminated boron nitride nanosheet with hyperbranched fluorine-containing polymer; the hyperbranched fluorine-containing polymer is obtained by polymerizing hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate and divinyl monomer. The battery diaphragm provided by the application comprehensively solves the technical problems of high resistance, low strength, easy filler agglomeration and poor thermal dimensional stability of the existing EFB battery polyethylene diaphragm, so that the prepared diaphragm can meet the use requirements of low resistance under the large-current charging and discharging working condition of the EFB start-stop battery diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a low-resistance EFB battery separator and its preparation method, belonging to the field of battery separator technology. Background Technology

[0002] The battery separator is a crucial component in lead-acid batteries, separating the positive and negative electrodes, preventing short circuits, and allowing ion transport. Although the separator does not directly participate in electrochemical reactions, its performance plays a decisive role in the battery's internal resistance, capacity, cycle life, and even safety. An ideal battery separator should possess the following characteristics: good chemical stability and resistance to sulfuric acid corrosion; a loose, porous structure to store electrolyte and provide ion transport channels; high mechanical strength to resist plate deformation and dendrite penetration; and low resistance to reduce energy loss during charging and discharging.

[0003] With the widespread adoption of automotive start-stop systems, EFB (enhanced flooded battery) batteries have gained widespread use due to their excellent deep-cycle performance and charge acceptance. Polyethylene (PE) separators, with their good chemical stability, low resistivity, and suitable mechanical strength, have become the mainstream choice for EFB battery separators. Existing PE separators are typically prepared using a wet stretching process: polyethylene resin, silica filler, and filler oil are melt-blended at high temperature, extruded, biaxially stretched, and then the filler oil is extracted with an organic solvent to form a microporous structure. PE separators prepared using this process have advantages such as uniform pore size and controllable thickness, and are currently the mainstream industrial technology.

[0004] Existing PE separators still have certain shortcomings in EFB battery applications. To ensure high-current discharge during battery operation, battery separators are typically required to have low resistance. For example, for start-stop EFB battery separators, a resistance of no more than 60 mΩ·cm² is usually required to ensure high-current discharge. The resistance of the separator is mainly determined by the resistance to ion transport within the separator pores, and increasing the effective porosity is one of the main ways to reduce separator resistance. To improve the porosity of PE separators and reduce resistance, a large amount of silica is currently added to the PE matrix, utilizing the "traces" left by silica particles after extraction as the microporous structure of the separator. However, silica is a hydrophilic inorganic particle with a surface rich in silanol groups (Si-OH), which has poor compatibility with the hydrophobic PE matrix. It is prone to agglomeration at high filling amounts. Agglomerated filler particles form stress concentration points, leading to a decrease in the puncture resistance of the membrane. At the same time, the increased interface defects increase the resistance, making it impossible to meet the contradictory requirements of high porosity, high strength, and low resistance. In addition, traditional spherical silica particles are randomly stacked in the PE matrix, and the pores formed after extraction have high tortuosity. The actual ion transport path is much larger than the apparent thickness of the membrane, which also leads to a bottleneck in reducing resistance.

[0005] To address the compatibility issue between silica and the PE matrix, existing technologies typically require the addition of compatibilizers such as silane coupling agents (e.g., KH-550, KH-560) or maleic anhydride-grafted polyethylene (MAH-g-PE). However, small-molecule coupling agents are easily lost with the filler oil during the extraction process in separator preparation, and the polar graft groups of MAH-g-PE are at risk of hydrolysis after prolonged immersion in strongly acidic electrolytes, leading to decreased interfacial adhesion and re-emerging filler agglomeration problems in later battery use. Furthermore, the addition of such compatibilizers increases formulation complexity and cost, and may introduce impurities into the battery system.

[0006] Furthermore, polyethylene has a melting point of approximately 130-140°C. Under conditions of battery thermal runaway or localized overheating, the PE separator is prone to thermal shrinkage, leading to a short circuit between the positive and negative electrodes. Existing technologies improve thermal stability by coating the separator surface with a ceramic layer (such as boehmite or alumina), but an interface always exists between the coating and the base film, which may detach during long-term cycling. Summary of the Invention

[0007] To address the aforementioned problems in the existing technology, the purpose of this invention is to provide a low-resistance EFB battery separator and its preparation method.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A low-resistance EFB battery separator is prepared from raw materials comprising the following components: Polyethylene resin: 135-165 parts by weight; Functionalized composite fillers: 200-250 parts by weight; Filler oil: 340-460 parts by weight; Initiator: 0.2-1 parts by weight; The functionalized composite filler is obtained by modifying hollow mesoporous silica, solid silica and aminated boron nitride nanosheets with a hyperbranched fluoropolymer; the hyperbranched fluoropolymer is obtained by polymerizing hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate and divinyl monomer.

[0009] The functionalized composite filler used in this invention includes: the ordered mesoporous structure of hollow mesoporous silica provides low-torsion channels for ion transport, and the hollow cavity serves as an electrolyte reservoir. The hollow mesoporous silica, combined with the auxiliary pore-forming effect of solid silica, forms a continuous, low-resistance ion transport network after extraction during membrane preparation, resulting in low-resistance membrane performance. The two-dimensional layered structure of aminated boron nitride nanosheets forms a physically cross-linked network within the PE matrix, and the hyperbranched fluoropolymer shell enhances interfacial bonding, thus giving the membrane high puncture resistance and thermal dimensional stability. Hollow mesoporous silica and solid silica... The three fillers, including aminated boron nitride nanosheets, are simultaneously modified by hyperbranched fluoropolymer coating in the same system, resulting in a completely consistent surface shell. The fluorinated segments of the hyperbranched fluoropolymer have good interfacial compatibility with the PE matrix, and the hyperbranched three-dimensional structure provides steric hindrance dispersion. Thus, there is no need to add additional coupling agents, compatibilizers, or plasticizers, avoiding the risk of small molecule additives being lost during the extraction process or precipitated during long-term battery operation. The synergistic effect among hollow mesoporous silica, solid silica, aminated boron nitride nanosheets, and hyperbranched fluoropolymer enables the separator to maintain high porosity while exhibiting excellent pore size uniformity and structural stability.

[0010] In one embodiment, the mass ratio of hollow mesoporous silica: solid silica: amino boron nitride nanosheets in the functionalized composite filler is 10-25:20-40:2-6, and the amount of the hyperbranched fluoropolymer is 10-20% of the total mass of hollow mesoporous silica, solid silica and amino boron nitride nanosheets.

[0011] In one embodiment, the aminated boron nitride nanosheets are obtained by first subjecting boron nitride nanosheets to plasma treatment in an oxygen atmosphere, and then grafting them with 3-aminopropyltriethoxysilane (KH-550).

[0012] In a preferred embodiment, the amount of 3-aminopropyltriethoxysilane in the aminated boron nitride nanosheets is 10-30% of the mass of the boron nitride nanosheets.

[0013] In a preferred embodiment, the preparation of the aminated boron nitride nanosheets includes the following steps: plasma treatment of boron nitride nanosheets under an oxygen atmosphere; dispersion of the resulting product in anhydrous toluene, addition of 3-aminopropyltriethoxysilane (KH-550), reflux reaction for 6-12 hours, centrifugation after the reaction, washing and drying to obtain aminated boron nitride nanosheets.

[0014] In a preferred embodiment, the plasma treatment is performed with a power of 80-120W, a treatment time of 50-70 seconds, and a vacuum level of 45-55Pa.

[0015] One embodiment of the preparation of the functionalized composite filler includes the following steps: Hollow mesoporous silica, solid silica, and amino boron nitride nanosheets were dispersed in anhydrous ethanol, and hyperbranched fluoropolymers were added. The mixture was stirred at 60-80℃ for 6-12 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain the functionalized composite filler.

[0016] One embodiment of the preparation of the hyperbranched fluoropolymer includes the following steps: Hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate, divinyl monomer and chain transfer agent were dissolved in 1,4-dioxane, a thermal initiator was added, and after freeze-thaw degassing, the polymer was polymerized at 60-80℃ for 12-24 hours. After the reaction was completed, the polymer was precipitated, washed and dried to obtain a hyperbranched fluoropolymer.

[0017] In a preferred embodiment, the mass ratio of hexafluorobutyl methacrylate: polyethylene glycol methyl ether methacrylate: divinyl monomer in the hyperbranched fluoropolymer is 5-10:3-6:0.5-2; the amount of chain transfer agent is 1-5% of the total mass of hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate, and divinyl monomer; and the amount of thermal initiator is 10-30% of the mass of chain transfer agent.

[0018] In a preferred embodiment, in the hyperbranched fluoropolymer, the divinyl monomer is diethylene glycol dimethacrylate, the chain transfer agent is a trithiocarbonate chain transfer agent (e.g., 2-(dodecyltrithiocarbonate)-2-methylpropionic acid), and the thermal initiator is azobisisobutyronitrile.

[0019] In a preferred embodiment, during the preparation of hyperbranched fluoropolymers, the freeze-thaw degassing refers to degassing the obtained reaction liquid by subjecting it to at least two cycles of liquid nitrogen freezing-vacuuming-thawing.

[0020] In one embodiment, the initiator in the battery separator is dicumyl peroxide (DCP). During the high-temperature melt blending process (twin-screw extrusion temperature 180-230℃), the free radicals generated by the decomposition of DCP can simultaneously capture hydrogen atoms on the PE molecular chain and attack the small number of double bonds or unsaturated end groups remaining in the shell of the hyperbranched fluoropolymer, thereby forming a chemical bond between the PE matrix and the functionalized filler, constructing an interfacial "bridging" effect, effectively enhancing the interfacial bonding force and inhibiting filler agglomeration.

[0021] In one embodiment, the polyethylene resin in the battery separator is ultra-high molecular weight polyethylene, for example, ultra-high molecular weight polyethylene with a molecular weight of 2 million to 3.5 million.

[0022] In one embodiment, the filling oil in the battery separator is white oil.

[0023] The preparation of a low-resistance EFB battery separator includes the following steps: a) Polyethylene resin, functionalized composite filler, initiator and filler oil are mixed and melt-extruded through a twin-screw extruder to obtain gel castings; b) The obtained castings are subjected to biaxial stretching, extraction, heat setting and winding in sequence to obtain the diaphragm product.

[0024] In one embodiment, in step a), the filler oil can be added after premixing with the solid material, or it can be added during the extrusion process through a liquid injection system. The solid material is a mixture of polyethylene resin, functionalized composite filler, and initiator. When using the premixing method, the solid material needs to be fully mixed in a high-speed mixer before adding the filler oil preheated to 60-80°C and stirring to form a uniform paste-like premix before feeding it into the extruder. When using the extrusion injection method, the solid material is added through the main feed port, and the filler oil preheated to 60-80°C is injected through the liquid injection system in the middle section of the extruder at a pressure of 5-15 MPa.

[0025] In one embodiment, the melt extrusion temperature is 180-230℃; during biaxial stretching, the stretching temperature for longitudinal stretching is 100-120℃ with a stretching ratio of 6-9 times, and the stretching temperature for transverse stretching is 115-135℃ with a stretching ratio of 7-10 times; the solvent used for extraction is dichloromethane or hexane; and the setting temperature is 120-135℃.

[0026] Compared with the prior art, the present invention has the following significant advantages: The functionalized composite filler used in the battery separator of this invention is obtained by modifying hollow mesoporous silica, solid silica, and aminated boron nitride nanosheets with a hyperbranched fluoropolymer. The hollow mesoporous silica provides ordered mesoporous channels, while the solid silica provides auxiliary pore formation, achieving low resistance. The two-dimensional layered network of aminated boron nitride nanosheets achieves high puncture resistance and low thermal shrinkage. The unified shell of the hyperbranched fluoropolymer achieves self-dispersion without compatibilizers. These three functions work synergistically to comprehensively solve the technical problems of high resistance, low strength, easy agglomeration of fillers, and poor thermal dimensional stability in existing EFB battery polyethylene separators. This results in a separator that meets the low resistance requirements of EFB start-stop battery separators under high-current charge-discharge conditions, demonstrating significant industrial application value. Detailed Implementation

[0027] The technical solution of the present invention will be further described in detail and completely below with reference to the embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. Example 1

[0028] 1) Preparation of hyperbranched fluoropolymers 100 parts by weight of hexafluorobutyl methacrylate (HFBMA, TCI (Shanghai) Chemical Industry Development Co., Ltd.), 45 parts by weight of polyethylene glycol methyl ether methacrylate (PEGMA, Mn≈300, Shanghai Maclean Biochemical Technology Co., Ltd.), 12 parts by weight of diethylene glycol dimethacrylate (DEGDMA, Shanghai Aladdin Biochemical Technology Co., Ltd.), and 4 parts by weight of trithiocarbonate chain transfer agent (2-(dodecyltrithiocarbonyl)-2-methylpropionic acid, Shanghai Meryl Biochemical Technology Co., Ltd.) were dissolved in 300 parts by weight of 1,4- 1.2 parts by mass of azobisisobutyronitrile (AIBN, Shanghai Aladdin Biochemical Technology Co., Ltd.) was added to dioxane and mixed thoroughly. After degassing by three cycles of liquid nitrogen freezing-vacuuming-thawing, the mixture was reacted in an oil bath at 70°C for 18 hours. After the reaction was completed, the mixture was cooled to room temperature. The resulting reaction solution was slowly added to excess petroleum ether under stirring to precipitate the product. The product was then centrifuged, and the resulting product was redissolved in a small amount of dichloromethane. Petroleum ether was added again to precipitate the product, and the mixture was centrifuged again. This process was repeated three times. The resulting product was dried under vacuum at 40°C to constant weight to obtain a hyperbranched fluoropolymer, denoted as HBFP.

[0029] (ii) Preparation of aminated boron nitride nanosheets 100 parts by mass of boron nitride nanosheets (average diameter 2 μm, thickness 3 nm, Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.) were placed in a plasma treatment instrument (power 100W, oxygen atmosphere, vacuum degree 50Pa) for 60 seconds for plasma treatment. The product was then removed and dispersed in 300 parts by mass of anhydrous toluene. 40 parts by mass of 3-aminopropyltriethoxysilane (KH-550, Dongguan Kangjin New Material Technology Co., Ltd.) were added, and the mixture was refluxed at 110℃ under nitrogen protection for 10 hours. After the reaction, the separated product was washed three times alternately with toluene and ethanol, and then dried under vacuum at 60℃ for 12 hours to obtain amino-modified boron nitride nanosheets, denoted as BNNS-NH2.

[0030] (III) Preparation of Functionalized Composite Fillers 25 parts by mass of hollow mesoporous silica (HMS, average particle size approximately 200 nm, shell mesopore diameter 5 nm, hollow cavity 150 nm, Shanghai Maclean Biochemical Technology Co., Ltd.), 45 parts by mass of solid silica (average particle size 15 μm, Evonik Industries AG, Germany) and 5 parts by mass of self-made aminated boron nitride nanosheets (BNNS-NH2) were dispersed together in 500 parts by mass of anhydrous ethanol and ultrasonically dispersed for 30 minutes to ensure uniform mixing of the three types of particles in the solution. 15 parts by mass of self-made hyperbranched fluoropolymer (HBFP) were added, and the mixture was stirred at 70 °C for 8 hours. After the reaction was completed, the mixture was centrifuged, and the resulting solid was washed three times with anhydrous ethanol and vacuum dried at 60 °C for 12 hours to obtain the functionalized composite filler, denoted as HMS / SiO2 / BNNS@HBFP.

[0031] (iv) Preparation of low-resistance EFB battery separator a) 150 parts by weight of polyethylene resin (ultra-high molecular weight polyethylene, weight average molecular weight 2.5 million, Celanese Corporation), 225 parts by weight of functionalized composite filler, and 0.6 parts by weight of initiator (dicumyl peroxide, DCP, Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to a high-speed mixer and mixed at room temperature for 15 minutes (550 r / min) to obtain a premix. The premix was then fed into a twin-screw extruder (length-to-diameter ratio 52) through a metering feeder, while 400 parts by weight of filler oil (white oil, NM40140, Beijing Newman Sino-German Petrochemical Co., Ltd.) was injected through a liquid injection port. The extruder temperatures were set as follows: Zone 1 170℃, Zone 2 190℃, Zone 3 210℃, Zones 4 to 8 205℃, and the die head temperature 200℃. The screw speed was 180 r / min. After melt blending, the material was extruded through a T-die and cast onto a cooling roller (cooling roller temperature 35℃) to obtain a gel-state cast sheet. b) The obtained castings are fed into a biaxial stretching machine for synchronous biaxial stretching. The longitudinal stretching temperature is 110°C, the transverse stretching temperature is 130°C, the preheating time is 300 seconds, the longitudinal stretching ratio is 8 times, and the transverse stretching ratio is 8.5 times. Then, the stretched separator is immersed in dichloromethane and extracted at 40°C for 300 seconds to remove the filler oil. Then, the extracted separator is heat-set at 120°C for 15 minutes, slit and wound up to obtain the low-resistance EFB battery separator (base thickness 0.25mm, total thickness 0.80mm). Example 2

[0032] The difference between this embodiment and Example 1 is that the content of each component in the diaphragm formulation is different. The specific formulation is: 135 parts by weight of polyethylene resin, 200 parts by weight of functionalized composite filler, 340 parts by weight of filler oil and 0.4 parts by weight of initiator; the rest is the same as in Example 1. Example 3

[0033] The difference between this embodiment and Embodiment 1 is that: 165 parts by weight of polyethylene resin, 250 parts by weight of functionalized composite filler, 460 parts by weight of filler oil, and 0.8 parts by weight of initiator; the rest are the same as in Embodiment 1.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the silica used in the functional filler is solid silica and does not contain hollow mesoporous silica. That is, the functional filler is obtained by modifying 70 parts by mass of solid silica and 5 parts by mass of aminated boron nitride nanosheets with hyperbranched fluoropolymer. The rest is the same as in Example 1.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that the functional filler used does not contain aminated boron nitride nanosheets. That is, the functional filler is obtained by modifying 25 parts by mass of hollow mesoporous silica and 45 parts by mass of solid silica with a hyperbranched fluoropolymer. The rest is the same as in Example 1.

[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that the functional filler used is obtained by modifying equal amounts of hollow mesoporous silica, solid silica and unmodified boron nitride nanosheets (without plasma treatment and KH-550 grafting) with equal amounts of silane coupling agent KH550 (3-aminopropyltriethoxysilane) instead of hyperbranched fluoropolymer. The rest is the same as in Example 1.

[0037] The battery separators prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to relevant standards, specifically as follows: 1) Resistance Test: Referring to Appendix B of GB / T 28535-2018, the AC impedance method was used at a frequency of 1000Hz. The electrolyte was a 1.28g / cm³ sulfuric acid solution, and the temperature was 25±0.5℃. The diaphragm sample was immersed in the electrolyte for 24 hours to reach complete equilibrium before testing. The diaphragm resistance (mΩ·cm) was measured. 2 ); 2) Puncture resistance test: Refer to Appendix C of GB / T 28535-2018, with a puncture needle diameter of 1.0 mm and a speed of 100 mm / min, and record the maximum force (N) required to puncture the diaphragm. 3) Porosity test: Referring to Appendix A of GB / T 28535-2018, the n-butanol absorption method was used. The membrane sample was immersed in n-butanol for 1 hour, and the porosity (%) was calculated by mass difference. 4) Heat shrinkage rate test: Cut the diaphragm sample into 10cm×10cm pieces, place them in a 130℃ oven for 1 hour, and measure the dimensional change rate (%) in the transverse (TD) and longitudinal (MD) directions. The test results are shown in Table 1.

[0038] Table 1 Performance test data of the battery separators prepared in Examples 1-3 and Comparative Examples 1-3

[0039] As can be seen from Table 1, the battery separators prepared in Examples 1-3 exhibit superior performance in terms of electrical resistance, puncture resistance, porosity, and thermal shrinkage compared to the battery separators in Comparative Examples 1-3. This may be because: 1) Regarding resistance: In Examples 1-3, hollow mesoporous silica with ordered channels and solid silica as an auxiliary pore-forming agent were used. The shell of the hollow mesoporous silica has an ordered mesoporous structure, providing an ordered, low-torsion channel for ion transport, with the actual ion transport path close to the apparent thickness of the membrane. At the same time, the hollow cavity of the hollow mesoporous silica can serve as an electrolyte reservoir, while the solid silica acts as an auxiliary pore-forming agent, enabling the hollow mesoporous silica channels to connect with each other and form a continuous, low-resistance ion transport network. In addition, the two-dimensional sheet structure of the aminated boron nitride nanosheets forms a physical cross-linking network in the PE matrix, and the hyperbranched fluoropolymer shell ensures that all fillers are uniformly dispersed in the PE matrix, avoiding filler agglomeration and pore blockage. The synergistic effect of these components enables the membrane resistance of Examples 1-3 to be as low as 21.5-25.8 mΩ·cm², exhibiting a significant low-resistance advantage. In contrast, in Comparative Example 1, no hollow mesoporous silica was added, and only solid silica was used to assist in pore formation. The solid silica was randomly stacked in the PE matrix, and the pores formed after extraction had high tortuosity. The actual ion transport path was much larger than the apparent thickness of the membrane, which led to an increase in the resistance of the membrane. In Comparative Example 2, although the ordered channels of hollow mesoporous silica can still reduce the tortuosity to some extent without the addition of aminated boron nitride nanosheets, the lack of two-dimensional lamellar reinforcing phase makes the filler prone to local agglomeration during processing, and some channels are blocked, resulting in an increase in the resistance of the membrane. Although Comparative Example 3 added both hollow mesoporous silica and solid silica, the ordered mesoporous channels of the hollow mesoporous silica still exerted their low tortuosity advantage to some extent. However, it was modified with the small molecule silane coupling agent KH550. KH550 can only form a monolayer on the filler surface, with limited steric hindrance, and cannot completely suppress the agglomeration of the filler under high filling volume. More importantly, KH550 is easily lost with the filler oil during the extraction process (the loss rate of silane coupling agents in hydrocarbon solvents can reach 30-50%), leading to the formation of agglomerates. The porous silica surface is re-exposed to the PE matrix, and there is a lack of effective interfacial bonding between the two. The entrances of the mesoporous channels, which were originally covered and protected by KH550, are partially blocked or collapsed due to agglomeration and processing stress, which impairs the connectivity of the channels. In contrast, the hyperbranched fluoropolymers used in Examples 1-3 can be firmly anchored to the PE matrix through a dual mechanism of physical entanglement and chemical grafting, and will not be lost during the extraction process, thus completely preserving the ordered mesoporous channels of HMS. Therefore, the membrane resistance of Comparative Example 3 is much higher than that of Examples 1-3. 2) Regarding puncture resistance and heat shrinkage: In Examples 1-3, aminated boron nitride nanosheets were added. These nanosheets were obtained by plasma-activating boron nitride nanosheets to introduce hydroxyl groups on their surface, followed by grafting of -NH2 active groups using KH-550. The aminated boron nitride nanosheets were then coated with a hyperbranched fluoropolymer to form a fluoropolymer shell. Under the initiation of dicumyl peroxide, the unsaturated double bonds in the hyperbranched fluoropolymer shell underwent a grafting / crosslinking reaction with the PE molecular chains, anchoring the aminated boron nitride nanosheets to the matrix through chemical bonds. The two-dimensional sheet structure of the aminated boron nitride nanosheets formed a physical crosslinking network in the PE matrix, effectively hindering crack propagation and molecular chain slippage, resulting in a puncture resistance of the membrane as high as 11.5-13.0 N. Furthermore, at high temperatures (130°C), the aminated boron nitride nanosheet network acted as a physical barrier to inhibit the thermal motion of the PE molecular chains, resulting in a thermal shrinkage rate (TD) of the membrane as low as 2.2-2.8%. In contrast, Comparative Example 2 did not add aminated boron nitride nanosheets, and relied solely on hollow mesoporous silica and solid silica to create pores. The lack of a two-dimensional sheet-like reinforcing phase resulted in a decrease in the puncture resistance of the membrane and an increase in the thermal shrinkage rate. In Comparative Example 3, the boron nitride nanosheets were not activated by plasma and grafted with KH-550, resulting in weak interfacial bonding with the PE matrix. Furthermore, the use of KH550 small molecule modifier could not construct a polymer shell compatible with the PE matrix. The interfacial tension between the boron nitride nanosheets and the PE matrix was large, making it difficult to disperse uniformly in the matrix and limiting the reinforcing effect. This led to a decrease in the puncture resistance of the membrane and an increase in the thermal shrinkage rate. 3) Porosity: In Examples 1-3, three types of fillers (hollow mesoporous silica, solid silica, and aminated boron nitride nanosheets) were simultaneously modified by hyperbranched fluoropolymer coating. All filler surfaces formed identical fluoropolymer shells. The fluorinated segments in these shells and the PE matrix are both non-polar / weakly polar systems, exhibiting natural compatibility. No additional small-molecule compatibilizers were needed; good interfacial bonding was achieved through physical entanglement. Furthermore, the three-dimensional branched structure of the hyperbranched fluoropolymer formed a thick steric hindrance layer on the filler surface, effectively inhibiting particle aggregation. Because the shells on the surfaces of the three fillers were completely identical, their dispersion behavior in the PE matrix was synchronized, and their interfacial properties were uniform, avoiding the differential aggregation problem common in multi-component filler systems. Therefore, the membranes in Examples 1-3 exhibited high porosity. While the fillers in Comparative Examples 1-2 were coated with hyperbranched fluoropolymers, the lack of key functional components (hollow mesoporous silica or boron nitride nanosheets) prevented the formation of a synergistic effect, resulting in a decrease in membrane porosity. Comparative Example 3, modified with a small-molecule KH550 silane coupling agent, could only form a monolayer on the filler surface, resulting in limited steric hindrance and an inability to effectively suppress agglomeration between fillers at high filler volumes. Furthermore, KH550 was easily lost with the filler oil during the extraction process, leading to a reduction in effective pore-forming sites and re-agglomeration of the filler in the final product. In addition, the lack of compatibility bridging between the amino groups of KH550 and the PE matrix resulted in weak interfacial bonding and poor filler dispersion, which also contributed to the decrease in membrane porosity in Comparative Example 3.

[0040] In summary, this invention constructs a functionalized composite filler with hyperbranched fluoropolymers for simultaneous coating. It utilizes the ordered mesoporous structure of hollow mesoporous silica to achieve low resistance, solid silica to assist in pore formation to form a continuous interconnected network, two-dimensional layered network of aminated boron nitride nanosheets to achieve high puncture resistance and low thermal shrinkage, and a unified shell of hyperbranched fluoropolymers to achieve self-dispersion without compatibilizers. The synergistic effect of these four components comprehensively solves the technical problems of high resistance, low strength, easy agglomeration of fillers, and poor thermal dimensional stability of polyethylene separators in existing EFB batteries.

[0041] Finally, it should be noted that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention shall fall within the scope of protection of the present invention.

Claims

1. A low-resistance EFB battery separator, characterized in that, It is prepared from raw materials containing the following components: Polyethylene resin: 135-165 parts by weight; Functionalized composite fillers: 200-250 parts by weight; Filler oil: 340-460 parts by weight; Initiator: 0.2-1 parts by weight; The functionalized composite filler is obtained by modifying hollow mesoporous silica, solid silica and aminated boron nitride nanosheets with a hyperbranched fluoropolymer; the hyperbranched fluoropolymer is obtained by polymerizing hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate and divinyl monomer.

2. The low-resistance EFB battery separator according to claim 1, characterized in that, In the functionalized composite filler, the mass ratio of hollow mesoporous silica: solid silica: amino boron nitride nanosheets is 10-25:20-40:2-6, and the amount of the hyperbranched fluoropolymer is 10-20% of the total mass of hollow mesoporous silica, solid silica and amino boron nitride nanosheets.

3. The low-resistance EFB battery separator according to claim 1, characterized in that, The aminated boron nitride nanosheets are obtained by first subjecting boron nitride nanosheets to plasma treatment in an oxygen atmosphere, and then grafting them with 3-aminopropyltriethoxysilane.

4. The low-resistance EFB battery separator according to claim 3, characterized in that, In the aminated boron nitride nanosheets, the amount of 3-aminopropyltriethoxysilane is 10-30% of the mass of the boron nitride nanosheets.

5. The low-resistance EFB battery separator according to claim 1, characterized in that, The preparation of the functionalized composite filler includes the following steps: Hollow mesoporous silica, solid silica, and amino boron nitride nanosheets were dispersed in anhydrous ethanol, and hyperbranched fluoropolymers were added. The mixture was stirred at 60-80℃ for 6-12 hours. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain the functionalized composite filler.

6. The low-resistance EFB battery separator according to claim 1, characterized in that, The preparation of the hyperbranched fluoropolymer includes the following steps: Hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate, divinyl monomer and chain transfer agent were dissolved in 1,4-dioxane, a thermal initiator was added, and after freeze-thaw degassing, the polymer was polymerized at 60-80℃ for 12-24 hours. After the reaction was completed, the polymer was precipitated, washed and dried to obtain a hyperbranched fluoropolymer.

7. The low-resistance EFB battery separator according to claim 6, characterized in that, In the hyperbranched fluoropolymer, the mass ratio of hexafluorobutyl methacrylate: polyethylene glycol methyl ether methacrylate: divinyl monomer is 5-10:3-6:0.5-2; the amount of chain transfer agent is 1-5% of the total mass of hexafluorobutyl methacrylate, polyethylene glycol methyl ether methacrylate and divinyl monomer; the amount of thermal initiator is 10-30% of the mass of chain transfer agent.

8. The low-resistance EFB battery separator according to claim 6, characterized in that, In the hyperbranched fluoropolymer, the divinyl monomer is diethylene glycol dimethacrylate, the chain transfer agent is a trithiocarbonate chain transfer agent, and the thermal initiator is azobisisobutyronitrile.

9. The low-resistance EFB battery separator according to claim 1, characterized in that, In the battery separator, the initiator is dicumyl peroxide.

10. A method for preparing the low-resistance EFB battery separator according to claim 1, characterized in that, Includes the following steps: a) Polyethylene resin, functionalized composite filler, initiator and filler oil are mixed and melt-extruded through a twin-screw extruder to obtain gel castings; b) The obtained castings are subjected to biaxial stretching, extraction, heat setting and winding in sequence to obtain the diaphragm product.